Ø¯Ø±Ø§Ø³Ø§Øª ÙÙŠ Ø¹Ù„ÙˆÙ… Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„Ù…Ø¹Ø§ØµØ±: Ù…ÙˆÙ‚Ù Ø§Ù„Ø³Ø± Ø³ÙŠØ¯ Ø£ØÙ…Ø¯ Ø®Ø§Ù† Ù…Ù† Ø¥Ø¹Ø¬Ø§Ø² Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… - Maghribi, Hamdan (State Institute of Islamic Studies (IAIN) Palu, 2016)
This paper deals with the I’jaz Alquran according to Sir Syed Ahmad Khan. It is concluded that Khan toughly emphasized his interpretation concept on rationalism. Khan also applied it for Quranic studies, such as emphasizing on rational and scientific facts that negate several metaphysical and invisible issues contained in Qur’an. Following his view on the prophets’ miracle which is irrational and unacceptable for human mind. Again, the concept of I’jaz Alquran is also one of Khan’s thought on rationality, though he acknowledged the great literary contents of Quran, as well he uncategorized it as a miracle. He then said that God’s challenge human to afford the similar verses to Qur’an is unclassified among I’jaz Qur’an, since God did the similar thing to the book of Torah as well. Unlike the opinion of majority Tafseer scholars, among the Salaf and Khalaf, they viewed that God’s challenge and the Quran high literature are evidence of I’jaz Quran.